An androgenic endocrine disruptor alters male mating behavior in the guppy (Poecilia reticulata). (6th October 2018) - Bertram, Michael G; Saaristo, Minna; Ecker, Tiarne E; Baumgartner, John B; Wong, Bob B M
Abstract : We show that exposure to a growth-promoting steroid used extensively in global beef production can alter male mating strategy in fish. Specifically, male guppies ( Poecilia reticulata ) exposed to an environmentally realistic level of the hormonally active pollutant 17β-trenbolone exhibited altered reproductive behavior and morphology, although male preference for greater female size was maintained at the dosage tested. Our findings highlight the potential for widespread disruption of reproductive processes in wildlife exposed to agricultural pollution. Abstract: Hormonally active chemical pollution threatens human and wildlife populations globally. However, despite the well-established capacity of endocrine-disrupting chemicals (EDCs) to alter reproductive traits, relatively few studies have examined the impacts of EDCs on mechanisms of sexual selection. This study investigated the effects of short-term exposure to an environmentally realistic level of 17β-trenbolone—a potent anabolic steroid used in livestock production worldwide—on male mate preference, reproductive behavior, and morphology in the guppy ( Poecilia reticulata ). Male guppies prefer to mate with larger females because such females are generally more fecund. Hence, males gain direct fitness benefits by being choosy. Here, we found no significant effect of 17β-trenbolone exposure on male courting behavior, with both unexposed and exposed males courting larger females more often. However, exposure to 17β-trenbolone significantly altered the amount of coercive copulatory behavior ("sneak" matings) performed. Specifically, while both unexposed and exposed males demonstrated a preference for larger females by conducting more sneaking attempts toward these females, exposed males carried out a greater number of sneaks toward large females than did unexposed males. Further, exposure resulted in increased male condition index (i.e., mass relative to length). Together, our results show for the first time that 17β-trenbolone can alter reproductive behavior and morphology in male fish at concentrations as low as 4 ng/L, highlighting the potential for disruption of reproductive processes in wildlife exposed to this potent agricultural contaminant.